2019
DOI: 10.1038/s41398-019-0543-1
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal structural brain network and hemisphere-specific changes in bulimia nervosa

Abstract: Bulimia nervosa (BN) is characterized by episodic binge eating and purging behaviors. Disrupted neural processes of self-regulation, taste-rewarding, and body image has been associated with the pathogenesis of BN. However, the structural basis for these behavioral and functional deficits remains largely unknown. We employed diffusion tensor imaging and graph theory approaches (including the nodal properties and network-based statistics (NBS)) to characterize the whole-brain structural network of 48 BN and 44 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…For example, connectivity between the ventral striatum and the insula and the frontal cortex (inferior and medial OFC) was shown to be increased in BN compared with HC ( Frank et al, 2016 ; Wang et al, 2019 ), while connectivity between the ventral striatum and the right basolateral amygdala (BLA) was reduced ( Frank et al, 2016 ). Network analysis in BN compared with HC shows that mesocorticolimbic pathways and other subcortical connections in the right hemisphere might be negatively affected in global efficiency ( Wang et al, 2019 ), a measure associated with parallel information processing ( Bullmore and Sporns, 2012 ). Pathways in the left hemisphere seem largely unaffected or even increased ( Wang et al, 2019 ).…”
Section: Brain Differences In Bn/bedmentioning
confidence: 99%
“…For example, connectivity between the ventral striatum and the insula and the frontal cortex (inferior and medial OFC) was shown to be increased in BN compared with HC ( Frank et al, 2016 ; Wang et al, 2019 ), while connectivity between the ventral striatum and the right basolateral amygdala (BLA) was reduced ( Frank et al, 2016 ). Network analysis in BN compared with HC shows that mesocorticolimbic pathways and other subcortical connections in the right hemisphere might be negatively affected in global efficiency ( Wang et al, 2019 ), a measure associated with parallel information processing ( Bullmore and Sporns, 2012 ). Pathways in the left hemisphere seem largely unaffected or even increased ( Wang et al, 2019 ).…”
Section: Brain Differences In Bn/bedmentioning
confidence: 99%
“…At present, it appears most plausible to expect that such interactions would be bidirectional and mutually reinforcing. The relationship between eating disorder symptoms and neural circuitry may be further explored using graph theory metrics such as “network density” and “average path length,” which could help elucidate both common and unique neural network properties that may underlie potential differences in eating-related psychopathology (e.g., Geisler et al, 2016 , Wang et al, 2019 ). Furthermore, because there does not appear to be one-to-one mapping between brain regions and psychological processes ( Anderson, 2014 ), other interpretations of our results may be possible.…”
Section: Limitations Future Directions and Conclusionmentioning
confidence: 99%
“…Studies have also reported altered brain structures in individuals with bulimia nervosa (BN) (Wang et al, 2019), and individuals with bingeeating disorder (BED) have been shown to respond differently to dopamine than BMI-matched controls (Wang et al, 2011), which may indicate aberrant neurostructural or neurofunctional responses to stimuli. Specifically, MRI studies of patients within the bulimic spectrum disorders have reported decreased cortical volume and/or diminished activity within the frontostriatal circuits-areas essential in self-regulation (Donnelly et al, 2018).…”
Section: Physical Activity To Induce Neurostructural Changes and Plasticitymentioning
confidence: 99%